Facile synthesis of novel CuCo2S4 nanospheres for coaxial fiber supercapacitors. Issue 48 (8th June 2017) - Wang, Qiufan; Liang, Xiao; Yang, Depeng; Zhang, Daohong
Abstract : A flexible coaxial supercapacitor was designed using CuCo2 S4 nanospheres on Ti wire, which exhibit satisfactory performances with high capacitance, excellent cycle stability and high energy density. Abstract : Flexible and highly efficient energy storage units act as one of the key components in portable electronics. In this work, based on CuCo2 S4 nanospheres, a flexible all-solid-state coaxial fiber supercapacitor is designed and produced via a low cost and facile method. The as-fabricated flexible device exhibits high specific capacitance, high energy density, excellent rate capability and outstanding long-term cycling stability. This approach can be an efficient strategy for the preparation of novel and low-cost electrodes for various applications.